Identification the effect of modified heat radiation model to human based on feyzin disaster - Nor Ahmad, Muhammad Akmal (2018)
The broad definition of BLEVE is that any liquefied vapour can cause a BLEVE. It can occur on catastrophic failure of a vessel containing even high-pressure hot water in a steam boiler, which is above its atmospheric boiling temperature. Such explosions can be very destructive of plant and equipment because they give rise to fragments from the exploding vessel. Any mechanism of catastrophic vessel failure include an impact damage, exposure to fire, fatigue, corrosion, and flawed construction can give rise to a BLEVE. A BLEVE also can give rise to a fireball. In this thesis, we are identified the effect of thermal or heat radiation toward human in Feyzin, France. By giving the parameters such as the distance of the explosion sources, time exposure and heat radiation value, the percentage of lethality found. We are proposed seven models, which is Point Source Model by Hymes and Lees, Static Model by TNO and CCPS, Dynamic Model, Maurer Correlation Model and Pool Fire Model. We are comparing the nearest value approach the data report from French Ministry of the Environment (ARIA, 2008). Besides, this thesis also discussing the relation between heat radiation with distance and time exposure where contributes and affecting the probit value and lethality.